Tauhid Sebagai Dasar Pengembangan Ilmu Pengetahuan - Bintan Kamila; Muhamad Arwansyah; Maftuh Ajmain (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to explain the concept of tauhid in the Islamic perspective as a foundation for the development of science, analyze the relationship between revelation, reason, and empirical experience in the tauhid paradigm towards the development of science, identify the factors causing the dichotomy between science and tauhid values in the development of modern science, and describe the implementation of tauhid values in the development of science and the practical life of Muslims in the modern era. The method used is library research with a descriptive-analytical approach to literature related to tauhid and Islamic epistemology. The results show that tauhid is the main foundation in the development of Islamic science because it integrates revelation, reason, and empirical experience in a balanced manner. Tauhid is not only theological but also becomes a philosophical, epistemological, and axiological foundation in building holistic knowledge. The thought of Syed Muhammad Naquib al-Attas emphasizes the concept of ta'dib, while Ismail Raji al-Faruqi affirms the Islamization of science to eliminate the dichotomy between science and religion.